Fundo Clima: construção e declínio? - Julianna Colonna; Heloisa de Camargo Tozato; Karoline Araújo; Neli Aparecida de Mello-Théry (Confins)
This article presents the budget evolution and the trajectory of the Climate Fund as an instrument of public action between 2009 and 2018. Created by Law nº 12.114 of 2009, it is defined as an economic instrument of the National Policy on Climate Change (Law n° 12.182/2009). The Ministry of the Environment is responsible for its management and operation of one of the two financing modalities. The second is operated by BNDES. The analyzes carried out in this article are based on budget data obtained through the federal government's SIGA Portal, on document analysis and on semi-structured interviews carried out between 2019 and 2020. Four main points are analyzed: budgetary evolution; the territorial distribution of resources; use of indicators for monitoring and evaluating projects; and finally, the comparability between the official data provided at different times by the different agencies involved. The main results show: i) the territorial concentration of resources operated by BNDES in the Southeast region and of resources operated by MMA in the Northeast region; ii) the decrease in the budget allocated to non-reimbursable projects, especially since 2013. The explanation for this decline lies in an insignificant government strategy setting GHG reduction targets requiring nothing more than control of illegal deforestation of the Amazon, which has weakened this instrument and the policy as a whole. The present study shows how the analysis of an instrument allows to highlight the creation of a half-measure that reinforces the schizophrenia of Brazilian environmental policy.